Proje yönetim danışmanlığı yapan firma bakışıyla proje yönetim sistemi ve uygulama örneği - Kocakulak, Murat (Fen Bilimleri Enstitüsü, 1997)
Türkiye gibi gelişmekte olan ülkelerde kaynakların kısıtlı olması, fınans bulmakta zorlukların yaşanması ve ileri teknolojinin imkanlarından her zaman yararlanılamaması gibi nedenlerle büyük projelerin gerçekleştirilebilmesi ancak yönetim alanında atılacak adımlarla mümkündür. Ülkemizde de bu anlamda bir proje yönetimi anlayışı, başta büyük şirketler olmak üzere diğer şirketlerde de hızla yaygınlaşmaktadır. Yapılan çalışmanın birinci bölümünde, çalışmanın amaç ve kapsamı açıklanmış, önemi vurgulanmıştır. İkinci bölümde, Proje yönetimi alanında danışmanlık hizmeti veren bir şirket gözüyle Proje Yönetimi kavramı ve sekiz unsuru ayrı ayrı açıklanmış, proje yönetiminde, planlama programlarında ve ABD Proje Yönetim Standartlarında geçen bazı kavramların tanımlan yapılmıştır. Üçüncü bölümde, Türkiye İş Bankası Genel Müdürlük Kompleksi İnşaatı Projesi, teknik ve fiziksel yönleriyle tanıtılmıştır. Aynı bölümde, şirket organizasyon şemaları hakkında bilgi de verilmiştir. Ayrıca Tepe-Tumer Steiner İş Ortaklığı'nın Türkiye İş Bankası ve IMS ile yaptığı sözleşmelerin iş programı ile ilgili maddeleri de irdelenmiştir. Dördüncü bölümde, Türkiye İş Bankası Genel Müdürlük Kompleksi İnşaatı Projesinin Detaylı İş Programı'nın hangi programda hazırlandığına değinilmiş, Detaylı İş Programı'nın hazırlanması anlatılmıştır. Beşinci bölümde, güncelleme ve bilgi alışveriş akış şemaları, raporlar ve formlar hakkında detaylı bilgi verilmiştir. Altıncı bölümde, genel bir değerlendirme yapılarak sonuçlar açıklanmış ve IMS tarafından önerilen sistemler tartışılmıştır.

In the developing countries like Türkiye, realization of big projects is possible only with high effort of the management because of the restricted resources, difficulty to find financial sources and difficulty to access to high technology process. In our country project management approach is being used widely thru the companies and mainly big companies. In the first section, the purpose and content of this work has been explained and its importance has been emphasized. In the second section, the definition of terminology's used into project management, planning programs; and Standart of Practice have been done thru project management consulting company approach. The concept of project and related eight items have been explained individually. A project is a unique, one-time endeavor with a specific start and end, and a strict budget. Generally, projects are performed by people who have limited experience working together as a team. It's also likely that some project participants will work off-site at several locations. These constraints often make project management difficult and complex. Project management is your response to the problems, delays, and changes, obstacles and sometimes opportunities that arise during the course of a project. The planning, controlling and managing are the basic key elements for project managements. These were explained below, Planning the project means thinking about and documenting what needs to be done, defining and coordinating specific activities and work tasks, preparing work schedules, assigning and allocating resources to competing activities, and developing an acceptable budget. Controlling the project means staying on course-measuring performance, suggesting corrective action when needed, evaluating options and devising workarounds. You inform the team about progress and advise them where their performance needs improvement. Then they make the improvements. Managing means during the project the involved people from different disciplines will be informed by complete accurate in time and enoughly detailed information regarding the project progress. The most important help and support provided by the management people to the project persons is their supply of accurate of complete information to the right person at the right time. XI Figure 1 shows, component processes of project management. These are described as below: Project Scope Management, includes the processes required to maintain control of the project in terms of the aims, goals, and objectives of the sponsor. It consists of authorization, scope planning, and scope definition, scope change management, and scope verification. Project Time Management, includes the processes required to ensure timely performance of the project. It consists of activity definition, activity sequencing, duration estimating, schedule development, and time control. Project Cost Management, includes the processes required to ensure that the project is completed within the approved budget. It consists of resource planning, cost estimating, cost budgeting, and cost control. Project Quality Management, includes the processes required to ensure that the project will satisfy the needs for which it was undertaken. It consists of quality planning, quality control, and quality assurance. Project Human Resource Management, includes the processes required to make the most effective use of the people involved with the project. It consists of organizational planning, staff acquisition, and team development. Project Communications Management, includes the processes required to ensure proper collection and dissemination of project information. It consists of communications planning, information distribution, progress reporting, and administrative closure. Project Risk Management, includes the processes concerned with identifying, analyzing, and responding to project risk. It consists of risk identification, risk quantification, response development, and risk control. Project Procurement Management, includes the processes required to acquire goods and services from outside the performing organization. It consists of procurement planning, solicitation planning, solicitation, source selection, contract administration, and contract close-out. In the third section, T.İş Bankası A.Ş. Construction projects of Head office have been presented thru technical and physical aspects. In the same section some information about company organization chart also has been given. The related items of the constructors signed between Tepe Turner Steiner with T.İş Bankası A.Ş. and IMS has been analyzed. Xll s o g-a? 'Sİ o '3 <« ts s S I II wwüü * * e e a, O a> CO CO O O o c o c o o a> tt o ç? o s o 3 u o o _Q o < a» t/3 ta O -- X11I In the fourth section, it has been studied that detailed work program of construction project of T.İş Bankası head office has been prepaid within which program. It has been described the preparation of detailed work program. Process for creating detailed work schedule includes 7 step. These are given below: - Start works - Relationships between parts of work - Make detailed list of activities - Add the activity information to P3 - Add the resource information to P3 - Analysis and reports - Finish works Figure 2 shows the preparation of detailed work program process. In the fifty sections, detailed information has been provided concerning updating and information exchange flow section schemes reports and forms. Table 1 shows; condense information about reports and forms. In the six sections, the problems faced during works and their solution with proposed systems have been described. In the same section a general evaluation has been done to disclose the results and some proposals have been brought up.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Danışmanlık hizmetleri; Proje yönetimi; Project management; Consulting companies